Effects of Limosilactobacillus reuteri on gastrointestinal microbiota, muscle fiber formation and meat quality of Sunit sheep - Ting Liu; Chenlei Wang; Mirco Corazzin; Taiwu Zhang; Maoqin Zhai; Yue Zhang; Qiaoge Zhang; Xin Zhao; Ye Jin; Lina Sun (Food Science of Animal Products)
Limosilactobacillus reuteri is a species of lactobacillus present in the gastrointestinal tract of animals and may contribute to the balance of intestinal flora. This study aimed to investigate the effects and correlations of L. reuteri on both intestinal flora and muscle fiber characteristics of Sunit sheep, with the objective of enhancing meat quality. Twelve 8-month-old Sunit sheep were randomly divided into two groups: control (fed without L. reuteri) and L. reuteri group. The results showed that L. reuteri had a significant positive impact on meat quality, particularly improving the tenderness of sheep meat compared with the control group, with values of 69.8 and 76.8 N, respectively (P < 0.05). L. reuteri group showed significantly more type I muscle fibers (23% vs. 13%) and higher succinate dehydrogenase activity than the control group, while lactate dehydrogenase activity was significantly lower (P < 0.05). The L. reuteri group showed significantly higher expression of genes encoding colonic epithelial nutrient transport (GPR43) and immune barrier function (Zonulin) than the control group. At the genus level, Alistipes and Methanobacterium were significantly different between L. reuteri and control groups (P < 0.05), with L. reuteri group showing an increase of 2.9 times and a decrease of 8.0 times compared to the control group, respectively. At the species level, Succiniclasticum ruminis and Bacteroides sp. 43_108 were significantly (P < 0.05) lower and higher, respectively in L. reuteri group than those in the control group. Butyric acid exhibited the highest concentration in L. reuteri group, reaching 7.52 mmol/L. In conclusion, supplementation with L. reuteri may affect muscle fiber characteristics, enhance intestinal health, and facilitate carbohydrate digestion of Sunit sheep. This study offers novel insights into the use of feed additives for improving meat quality.